Girls' business friendship and bullying in schools - Sleeth, Shannon; Collins, Cath; Garner, Simon; Leigh, Richard; Video Education Australasia (Australia : Video Education Australasia, 2005)
Girls can be the best of friends or the worst of enemies. Instead of physical aggression typical of boys, girls tend to use covert, indirect techniques that are equally devastating to the victim. This program examines some of these startegies and help us to understand why some girls adopt these methods of expression
Title from title screen
Executive producer, Mark McAuliffe ; editor, Shannon Sleeth ; sound, Wayne Martin, Alexy Gudimenko
Voice over: Jessica Birnbaum
DVD Format
Keywords: Bullying in schools; Bullying